Molecular photoswitches: chemistry, properties, and applications - Pianowski, Zbigniew L. (Wiley-VCH, 2022)
A comprehensive overview about the emerging field of photoswitches and their applications in materials science and biology Molecular Photoswitches guides the reader through the basic molecular structures of photochromic compounds and their applications in the area of photoresponsive materials as well as in the biological context. The initial chapters describe individual classes of molecular photoswitches, introducing their principles of photochromism, typical switching wavelengths, thermal stability of photoisomers and other key information, which is ordinarily spread in the literature. These classes comprise i.a. azobenzenes, diazocines, arylazoheterocycles, arylhydrazones, indigoids, photochromic imines, or acylhydrazones. The book also covers: Catalysis with molecular switches Applications in photochromic porous materials, liquid crystals, or nanoparticles Light-responsive molecular machines, logic devices, and molecular magnets Photomodulation of biological systems: photoswitchable biopolymers, lightmodulated antibiotics, cytotoxins, ion channel inhibitors, light-propelled artificial muscles, and computationally designed photochromic proteins This two-volume work is a valuable guide for researchers and non-experts working in the field of photochemistry, organic chemistry, catalysis, materials science, biology, and medicine.--